Kynurenic acid and its derivatives are able to modulate the adhesion and locomotion of brain endothelial cells - Lajkó Eszter (JOURNAL OF NEURAL TRANSMISSION, 2018)
The neuroprotective actions of kynurenic acid (KYNA) and its derivatives in several neurodegenerative disorders [characterized by damage to the cerebral endothelium and to the blood–brain barrier (BBB)] are well established. Cell–extracellular matrix (ECM) adhesion is supposedly involved in recovery of impaired cerebral endothelium integrity (endothelial repair). The present work aimed to investigate the effects of KYNA and its synthetic derivatives on cellular behaviour (e.g. adhesion and locomotion) and on morphology of the GP8 rat brain endothelial cell line, modeling the BBB endothelium. The effects of KYNA and its derivatives on cell adhesion were measured using an impedance-based technique, the xCELLigence SP system. Holographic microscopy (Holomonitor™ M4) was used to analyse both chemokinetic responses and morphometry. The GP8 cells proved to be a suitable model cell line for investigating cell adhesion and the locomotion modulator effects of kynurenines. KYNA enhanced cell adhesion and spreading, and also decreased the migration/motility of GP8 cells at physiological concentrations (10−9 and 10−7 mol/L). The derivatives containing an amide side-chain at the C2 position (KYNA-A1 and A2) had lower adhesion inducer effects compared to KYNA. All synthetic analogues (except KYNA-A5) had a time-dependent inhibitory effect on GP8 cell adhesion at a supraphysiological concentration (10−3 mol/L). The immobilization promoting effect of KYNA and the adhesion inducer activity of its derivatives indicate that these compounds could contribute to maintaining or restoring the protective function of brain endothelium; they also suggest that cell–ECM adhesion and related cell responses (e.g. migration/motility) could be potential new targets of KYNA. © 2018 Springer-Verlag GmbH Austria, part of Springer Nature